Peran Dari OSCE Minsk Group Dalam Mediasi Konflik Di Wilayah Nagorno-Karabakh - Prasada Arnaya, I Putu Angga; Anom Wiranata, I Made; Intan Prameswari, Anak Agung Ayu (Program Studi Hubungan Internasional FISIP Universitas Udayana, 2015)
ABSTRACK Ethnic conflict is one of the most frequent forms of conflict that arises after the desolation of the Soviet Union. Ethnic differences between regions in the former Soviet Union is a major cause of ethnic conflict. Nagorno-Karabakh is one of territory of the former Soviet Union that face ethnic conflict. Organisation for Security and Cooperation in Europe (OSCE) as the world’s largest regional security thinks the need to do the mediation of Nagorno-Karabakh conflict involving Armenia and Azerbaijan through its institution, OSCE Minsk Group. OSCE Minsk Group co-chaired by United States of America, France, and Russia. This study aims to describe OSCE Minsk Group’s role as mediator in the conflict of Nagorno-Karabakh. This study assessed by using ethnonationalist and mediation as concepts within 2009-2013 as timeline. Key words: Nagorno-Karabakh, Armenia, Azerbaijan, OSCE Minsk Group